Efficacy and safety of prophylactic HPV vaccines. A Cochrane review of randomized trials - M. Arbyn; L. Xu (Taylor & Francis Group, 2018)
Introduction: Recently, the evidence on efficacy and safety of prophylactic HPV vaccines derived from randomized trials was published in the Cochrane database of Systematic reviews. A summary of this Cochrane review is presented below. Areas covered: Only trials involving mono-, bi-, and quadrivalent HPV vaccines were included. Trials evaluating the nonavalent vaccine were excluded since women in the control group received the quadrivalent vaccine. Main efficacy outcomes were: histologically confirmed cervical precancer lesions distinguishing those associated with vaccine HPV types and any cervical precancer. Exposure groups were: women aged: 15-26 or 24-45 years being initially negative for high-risk HPV (hrHPV) or negative for the vaccine types and women unselected by HPV status. Expert commentary: All evaluated vaccines offered excellent protection against cervical intraepithelial neoplasia of grade 2 or 3 (CIN2 or CIN3) and adenocarcinoma in situ associated with HPV16/18 infection in young women who were not initially infected with hrHPV or HPV16/18. Vaccine efficacy was lower when all women regardless of HPV DNA status at enrollment were included. In young women, HPV vaccination protected also against any cervical precancer but the magnitude of protection was lower than against HPV16/18 associated cervical precancer. Vaccine efficacy was lower in mid-adult (aged 24-45 years) women. No protection against cervical precancer was found in mid-adult women unselected by HPV DNA status at enrollment. Trials were not empowered to address protection against cervical cancer. Occurrence of severe adverse events or adverse pregnancy outcomes was not significantly higher in recipients of HPV vaccines than in women included in the control arms.